Sciatic nerve analysis in thyroid hormone transporters Mct8 and Oatp1c1 knockout mice - Steffen Mayerl; Andrea Alcaide Martin; Reinhard Bauer; Heike Heuer (European Thyroid Journal, 2025)
Objective: Mutations in the thyroid hormone (TH) transporter monocarboxylate transporter 8 (MCT8) cause Allan–Herndon–Dudley syndrome (AHDS), a severe form of psychomotor retardation with muscle hypoplasia and spastic paraplegia as key symptoms. These abnormalities have been attributed to impaired TH transport across brain barriers and into neural cells, thereby affecting brain development and function. Likewise, Mct8/Oatp1c1 (organic anion-transporting polypeptide 1c1) double knockout (M/Odko) mice, a well-established murine AHDS model, display a strongly reduced TH passage into the brain as well as locomotor abnormalities. To which extent the peripheral nervous system is affected by combined MCT8/OATP1C1 deficiency has not been addressed. Methods: Using the sciatic nerve as a model, we studied the spatiotemporal expression of TH transporters as well as the sciatic thyroidal state, sciatic nerve myelination and function in M/Odko mice by immunofluorescence, qPCR, Western blotting and electrophysiology. Results: We detected MCT8 protein expression in sciatic nerve axons, whereas OATP1C1 expression was observed in a subset of endothelial cells early in postnatal development. The absence of MCT8 and OATP1C1 did not alter the thyroidal state of isolated nerves at P12. Moreover, electrophysiological studies did not disclose any significant alteration in sciatic nerve signal propagation parameters in adult M/Odko mice. Although Schwann cell numbers were similar, Western blot analysis showed a mild form of hypermyelination in adult M/Odko mice. Conclusions: Altogether, our data point to a largely unaffected sciatic nerve structure and function in the absence of MCT8 and OATP1C1.